NLRP3 Sensing of Diverse Inflammatory Stimuli Requires Distinct Structural Features - Rahman, Tabassum; Nagar, Abhinit; Duffy, Ellen B.; Okuda, Kendi; Silverman, Neal; Harton, Jonathan A. (Frontiers in Immunology, 2020)
The NLRP3 inflammasome is central to host defense and implicated in various inflammatory diseases and conditions. While the favored paradigm of NLRP3 inflammasome activation stipulates a unifying signal intermediate that de-represses NLRP3, this view has not been tested. Further, structures within NLRP3 required for inflammasome activation are poorly defined. Here we demonstrate that while the NLRP3 LRRs are not auto-repressive and are not required for inflammasome activation by all agonists, distinct sequences within the NLRP3 LRRs positively and negatively modulate inflammasome activation by specific ligands. In addition, elements within the HD1/HD2 “hinge” of NLRP3 and the nucleotide-binding domain have contrasting functions depending upon the specific agonists. Further, while NLRP3 1-432 is minimally sufficient for inflammasome activation by all agonists tested, the pyrin and linker domains (1-134) function cooperatively and are sufficient for inflammasome activation by certain agonists. Conserved cysteines 8 and 108 appear important for inflammasome activation by sterile, but not infectious insults. Our results define common and agonist-specific regions of NLRP3 that likely mediate ligand-specific responses, discount the hypothesis that NLRP3 inflammasome activation has a unified mechanism, and implicate NLRP3 as an integrator of agonist-specific, inflammasome activating signals.